EXPLORING CRANIOFACIAL DIVERSITY IN SOUTH INDIAN ADULTS: AN INNOVATIVE INVESTIGATION UTILIZING A DATASET OF 2000 ORTHOPANTOMOGRAM IMAGES - Dr K Mahadevan, G.Vennila, Mr.L. Sathish Kumar, Mr. Silambarasan Sekar, Dr.Abilasha Deenadayalan (Chelonian Research Foundation, 2023)
Introduction: This study delves into the intricate nuances of craniofacial morphology within the South Indian adult population, aiming to elucidate the unique dental and skeletal patterns that characterize this diverse regional demographic. In a comprehensive analysis, we explore the dimensions of dental structures, dental arch morphology, and skeletal features, utilizing a dataset comprising 2000 orthopantomogram (OPG) images. This research not only contributes to the broader field of dental anthropology but also has practical implications for clinical dentistry and orthodontics, particularly in the context of the South Indian population. Methodology: Our research methodology involves advanced image processing techniques, including landmark identification and geometric morphometrics, applied to the collected OPG images. This enables the extraction of quantitative data, facilitating a meticulous examination of dental and skeletal parameters. The statistical framework adopted encompasses descriptive statistics to unveil central tendencies and variations across multiple parameters. Furthermore, inferential statistics, such as correlation analyses and multivariate tests, are employed to discern intricate relationships between different craniofacial features. Results: In the dental domain, our analysis reveals distinctive variations in tooth size, dental arch dimensions, and related parameters. Concurrently, our skeletal analysis encompasses measurements of cranial dimensions and mandibular morphology, offering profound insights into the underlying skeletal variations within the population. The richness of the dataset allows for a detailed exploration of the craniofacial landscape, providing a valuable resource for future studies and interventions. Discussion: The outcomes of this study carry implications for both clinical practice and anthropological research. By uncovering population-specific variations in craniofacial morphology, our research not only adds to the existing body of knowledge but also underscores the need for nuanced considerations in clinical settings. The observed variations prompt a discussion on the potential impact on orthodontic treatments and dental procedures tailored to the South Indian population. Conclusion: In conclusion, this study not only contributes valuable insights into the craniofacial morphology of the South Indian adult population but also establishes a foundation for future research endeavors. The comprehensive dataset and detailed analyses serve as a robust reference point for clinicians, researchers, and anthropologists, emphasizing the importance of understanding regional variations in providing effective and culturally sensitive healthcare interventions.